Neonatal cholestasis – A case report on congenital bile acid synthetic defect type 4 and severe anemia - Saxena , Sufla (Indian Journal of Case Reports, 2022)
Congenital defects of bile acid synthesis are rare disorders that cause progressive liver dysfunction. We present a case of alpha methylacyl-CoA racemase (AMACR) deficiency with non-spherocytic hemolytic anemia who presented with rapidly progressive severe cholestasis and liver failure with normal gamma-glutamyl transferase levels. After extensive investigation, he was found to have AMACR deficiency with HBB gene mutation associated with non-spherocytic hemolytic anemia possibly explaining the severity of the disease. To the best of our knowledge, a similar association has not been reported so far.